2005
DOI: 10.1051/animres:2004039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cereal sources and processing in diets for the growing rabbit. II. Effects on performances and mortality by enteropathy

Abstract: -The effects of the quality of the dietary starch on growth performance and mortality were studied on five experimental sites on 1784 growing rabbits (446 per diet). Four iso-fibre diets varying in starch nature (W-wheat, B-barley, M-maize, EM-Extruded maize) were compared. The diets were given ad libitum from weaning (30 to 35 d. of age, depending on the site) to slaughter (68 to 71 d). From weaning to 49 days of age, the weight gain did not differ significantly according to the starch source (mean = 48.6 g·d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 11 publications
(18 reference statements)
1
18
0
Order By: Relevance
“…Moreover, a large-scale study using a network of six experimental breeding units (GEC French group) demonstrated that only the fibre level plays a role in digestive trouble and not the starch level (Gidenne et al, 2004b). Furthermore, by comparing iso-fibre diets but with several starch sources varying in their intestinal digestion (maize, wheat, barley), Gidenne et al (2005) observed no effect of starch ileal flow on diarrhoea incidence in the weaned rabbit. Fibre intake thus plays a major role in determining digestive trouble in the classically weaned rabbit (28 to 35 days old).…”
Section: Brief Overview Of Polymers Of the Plant Cell Wall: Definitiomentioning
confidence: 92%
“…Moreover, a large-scale study using a network of six experimental breeding units (GEC French group) demonstrated that only the fibre level plays a role in digestive trouble and not the starch level (Gidenne et al, 2004b). Furthermore, by comparing iso-fibre diets but with several starch sources varying in their intestinal digestion (maize, wheat, barley), Gidenne et al (2005) observed no effect of starch ileal flow on diarrhoea incidence in the weaned rabbit. Fibre intake thus plays a major role in determining digestive trouble in the classically weaned rabbit (28 to 35 days old).…”
Section: Brief Overview Of Polymers Of the Plant Cell Wall: Definitiomentioning
confidence: 92%
“…The technology of extrusion clearly improved the digestion of maize starch, but it possibly affected feed intake before weaning. In the future, growth performances and mortality using a high number of animals in a network of experimental stations will be studied (a second part of this study [16]). …”
mentioning
confidence: 99%
“…This may be related to the small effect of the increase in potato starch on the quantity of undigested starch entering in the caecum and on the caecal microbial population previously described. The preceding studies reported higher ileal starch concentrations (5 to 10 times higher, Gidenne et al, 2005a) that were not associated with a higher frequency of digestive troubles in the growing rabbit (Gidenne et al, 2005b). The small effect observed on digestive troubles could be linked to the similar fibre level among the PSO, PS7 and PS14 diets.…”
Section: Discussionmentioning
confidence: 76%